2012
DOI: 10.1044/1092-4388(2012/11-0236)
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of a Parent-Implemented Language Intervention for Children With Language Impairments Using Empirical Benchmarks: A Pilot Study

Abstract: The results of this preliminary study indicate that parent-implemented interventions may be an effective treatment for children with expressive and receptive LI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
116
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 30 publications
(29 reference statements)
2
116
0
3
Order By: Relevance
“…However, other quality ratings were less reliably reported. Intensity of recasts was reported for only 1/7 (14%) of the studies added (Roberts & Kaiser, 2012), and blinding was similarly reported for only 1/7 studies . Treatment fidelity was adequately reported for 3/7 (43%) studies.…”
Section: Meta-analysismentioning
confidence: 51%
See 4 more Smart Citations
“…However, other quality ratings were less reliably reported. Intensity of recasts was reported for only 1/7 (14%) of the studies added (Roberts & Kaiser, 2012), and blinding was similarly reported for only 1/7 studies . Treatment fidelity was adequately reported for 3/7 (43%) studies.…”
Section: Meta-analysismentioning
confidence: 51%
“…The seven Later Efficacy/Effectiveness studies included five package interventions and two recast-only interventions. In contrast to the previous analysis, only one of these studies (Roberts & Kaiser, 2012) compared the experimental group to an alternate-treatment control group. Note that Fey et al (1993) contributed two outcomes to the averages discussed here because of the study design; one participant group received recast-only intervention implemented by parents, and the other received a package intervention implemented by a clinician.…”
Section: Meta-analysismentioning
confidence: 90%
See 3 more Smart Citations